Pengembangan Media Interaktif Articulate Storyline 3 Mata Pelajaran Bahasa Indonesia Kelas IV SD Negeri 3 Margomulyo - Amanda Kartika Sari; Nugrananda Janattaka (Journal on Education, 2024)
The 21st century is a time of globalization, signified by the rapid development of technology and communication. This has led to a growing need for interactive learning media in educational activities. A research project has been conducted to make Indonesian language learning more engaging. The research method used the Research and Development (R&D) approach, specifically referring to the ADDIE model, which consists of five stages of implementation. The research employed validation sheets from media and material experts, as well as a questionnaire to assess student responses, involving 14 students from SDN 3 Margomulyo. The results of the study show that interactive media created using the Articulate Storyline 3 application for fourth-grade Indonesian language subjects is highly valid, receiving an average approval rating of 91% from media experts and 92% from material experts. The field trial also resulted in a high student response rating of 92.6%, indicating the media's high validity. As a result, the development of interactive media through the Articulate Storyline 3 application is deemed highly viable for use as an interesting and innovative learning tool for Indonesian language subjects in fourth grade at SDN 3 Margomulyo.